The Development of English Language Learning Multimedia Based on Problem-Based Learning Using Linktree - Hernita Jusepa Br Tompul; Samsidar Tanjung; Dina Ampera (Jurnal Educative: Journal of Educational Studies, 2025)
This research aimed to develop English multimedia learning based on the Problem-Based Learning (PBL) model using the Linktree platform for instructional text material at SMP Swasta Santo Thomas 1 Medan. The study followed the ADDIE development model without testing effectiveness, focusing solely on producing a feasible and relevant learning product. The analysis phase revealed that students encountered significant difficulties in understanding the structure and language features of instructional texts, and that the learning process lacked interactive digital media. In response, a multimedia product was developed by integrating PBL principles to foster student collaboration and critical thinking. The Linktree platform was selected to structure all learning materials, assignments, and activities into a single accessible interface. The developed media was validated by subject matter experts, instructional design experts, and media experts, all of whom rated it as 'very feasible.' Subsequent individual, small group, and large group trials involving students also showed high levels of acceptance and usability. These findings indicate that the developed media is practical and appropriate for supporting 21st-century English learning at the secondary school level.